The Causal Effect of Radical Right Success on Mainstream Parties' Policy Positions: A Regression Discontinuity Approach - Tarik Abou-Chadi; Werner Krause (British Journal of Political Science, 2020)
This article investigates how the success of radical right parties affects the policy positions of mainstream parties. We do this using a regression discontinuity approach that allows us to causally attribute mainstream parties' positional changes to radical right strength independent of public opinion as a potential confounder. Making use of exogenous variation created through differences in electoral thresholds, we empirically demonstrate that radical right success, indeed, causally affects mainstream parties' positions. This is true for mainstream left as well as mainstream right parties. These findings make an important contribution to the broader literature on party competition as they indicate that other parties' behavior and not only public opinion plays a crucial role in explaining parties' policy shift.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.; doi:10.7910/DVN/KYSD5S
Keywords: 330; radical right; party competition; immigration